Pembelajaran PAI berbasis Moving Class di SMP Negeri 1 Gudo Jombang - Moch. Sya'roni Hasan; Dian Eka Saputri (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2020)
Moving Class is one of the learning models that moves between classes or places of study. This learning model is applied to the learning of Islamic religious education in SMP Negeri 1 Gudo. The purpose of this study is to describe the implementation of the Moving Class in the learning of Islamic Religious Education in SMP Negeri 1 Gudo Jombang. Thus the conclusions of the results of the study are: The Implementation of Moving Classes in Islamic Religious Education learning in SMP Negeri 1 Gudo is one of the efforts to create a new learning process, so that it is not saturated because of the monotony and routine of providing unchanging facilities (classrooms). This junior high school located in Gudo has a goal in implementing moving classes in Islamic religious education learning, which is to change the awkward learning atmosphere to be active, students can argue and can directly practice the material conveyed by the teacher. In learning Islamic religious education a lot of theories that need to be developed, therefore not only understanding the theory, but is also expected to be able to apply in life in society.